ANALISIS BATASAN KEWENANGAN PRESIDEN DALAM MEMBENTUK PERATURAN PRESIDEN MENURUT UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Abdurrahman, Rizal; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This legal research analyzes and examines the limits of the Presidential power in the establishment of the Presidential Regulation according to Law Number 12 of 2011 Concerning the Establishment on Laws and Regulations. This research is a normative research viewed from prescriptive characteristic by statute and conceptual approach. The types of data collected include primary and secondary legal materials through library research. The data is analyzed by deductive method. The results indicates that the Presidential Regulation can only be established within the framework of (1) enjoined the establishment of both expressly (mentioned forms and institutions) as well as unambiguous (only mentioned institutions) by the Act; (2) as the implementing regulation on the Government Regulation either delegated directly or according to the needs of further regulation; and (3) as an autonomous regulation in order to organize the power of state government. The form of autonomous presidential regulation can only be established if (a) is really a technical, and (b) solely for the internal purpose of administration in order to enforce the provisions of the laws and regulations. In addition, Presidential Regulations may also be established to the extent of providing public benefit and in accordance with the Good Governance Principles.